Pengaruh Iklan Meta Ads, Harga, dan Kualitas Produk Terhadap Minat Beli Online Produk Digital: Studi Kasus Instagram @Cuantanpakamera - Kevin Boby Andika; RA Marlien; Andreas Tigor Oktaga (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the influence of Meta Ads, price, and product quality on the online purchase intention of digital products marketed through the Instagram account @cuantanpakamera. This study employs a quantitative approach. The population of this study consists of all 31,800 followers of the @cuantanpakamera Instagram account. The sampling technique used was purposive sampling, involving 125 respondents. Data analysis was conducted using multiple linear regression aided by the Statistical Package for Social Sciences (SPSS) 22.0 for Windows. The results indicate that Meta Ads, price, and product quality variables have a positive and significant effect on online purchase intention. Meta Ads was identified as the most dominant factor influencing online purchase intention. The coefficient of determination (R²) value of 0.663 indicates that the independent variables are able to explain 66.3% of the variation in online purchase intention, while the remaining 33.7% is explained by other factors such as consumer trust, brand awareness, and so forth. This study emphasizes the importance of implementing effective digital advertising strategies and consistent product quality management to enhance consumer purchase intention in the era of social media-based marketing.